Clinical Examination Skills for Healthcare Professionals. - Ranson, Mark (M & K Update Ltd, 2014)
Today, an increasing number of healthcare professionals (including nurses, midwives and members of many allied professions) have to conduct the vital first stage in a patient's journey - taking a clinical history and conducting an effective physical examination. This book offers clear, practical guidance on the fundamentals of clinical examination for any practitioner who wishes to understand their patient's specific needs and to plan appropriate care. Recognising that readers will come from a diverse range of clinical backgrounds and roles, the opening chapter (on consultation and the skills.